Nuclear service water piping : Oskarshamn Nuclear Power Plant, Figeholm, Sweden. (Nickel Institute, 1995)
This booklet provides case studies of nuclear service water piping system in Oskarshamn Nuclear Power Plant.
Keywords: Oskarshamnsverket (Sweden); Nuclear power plants -- Piping.; elektronické knihy; electronic books